The consequences of use of ritalin without a medical prescription - Schuindt, Alessandra de Almeida Pontes (2021)
It aimed to evaluate the use of the medication Ritalin® in academics without prescription and what effects this medication can cause in the human body. This research aims to show the importance of the correct use of methylphenidate medication, and the accurate diagnosis for its use, besides proving that it should only be used with a doctor's prescription, because it can cause serious side effects.Methodology: A literature review study was carried out using the ABNT standard, using databases, SCIELO (Scientific Electronic Library Online), MEDLINE, LILACS, Academic Google, Bireme, Ebsco Host, Pubmed, books and 17 articles published between 2011 and 2021 in Portuguese, English and Spanish. The Keywords are “Ritalin®”, “methylphenidate”, “adverse effects”, and “consequences”, in Portuguese, Spanish and English, related to the themes, isolated and grouped together. Articles that met the following criteria were included: (1) studies that focus on the use of Ritalin® by students without a medical prescription (2) studies that are available in full text.  Results: The consequences of using methylphenidate without a medical prescription, or even without monitoring by a multidisciplinary team for the treatment of the Disorder for which the medication is indicated, are abuse and dependence, masking evolutionary diseases, especially those of mental health such as anxiety and panic syndrome, decreased appetite, decreased sleep, leading to decreased sleep quality, occasional and transient cardiovascular problems, such as increased systolic pressure, heart rate and respiratory rate, if the individual already has preexisting heart problems, it can lead to death. Conclusion: The use of Ritalin® indefinitely and indiscriminately causes neurological, physical and mental consequences in people who consume it, making us think about the intake and sale of this medication to publics such as university students, and that the prescription and correct medical follow-up are indispensable